Seagrass Removal Leads to Rapid Changes in Fauna and Loss of Carbon - Githaiga, Michael N.; Frouws, Anna M.; Kairo, James G.; Huxham, Mark (Frontiers in Ecology and Evolution, 2019)
Seagrass habitats are important natural carbon sinks, with an average of 14 kg C m−2 buried in their sediments. The fate of this carbon following seagrass removal or damage has major environmental implications but is poorly understood. Using a removal experiment lasting 18 months at Gazi Bay, Kenya, we investigated the impacts of seagrass loss on sediment topography, hydrodynamics, faunal community structure and carbon dynamics. Sediment pins were used to monitor surface elevation. The effects of seagrass removal on water velocity was investigated using Plaster of Paris dissolution. Sediment carbon concentration was measured at the surface and down to 50cm. Rates of litter decay at three depths in harvested and control treatments were measured using litter bags. Drop samples, cores, and visual counts of faunal mounds and burrows were used to monitor the impact of seagrass removal on the epifaunal and infaunal communities. Whilst control plots showed elevation, harvested plots were eroded (7.6 ± 0.4 and -15.8 ± 0.5 mm yr-1 respectively, mean ± 95% C.I). Carbon concentration in the surface sediments was significantly reduced with a mean carbon loss of 1.13 Mg C ha-1 in the top 5cm. Because sediment was lost from harvested plots, with a mean difference in elevation of 3cm, an additional carbon loss of up to 22.9 ± 2.4 Mg C ha-1 may have occurred over the 18 months. Seagrass removal had rapid and dramatic impacts on infauna and epifauna. There was a loss of diversity in harvested plots and a shift towards larger bodied, bioturbating species, with a significant increase in mounds and burrows. Buried seagrass litter decomposed significantly faster in the harvested compared with the control plots. Loss of seagrass therefore lead to rapid changes in sediment dynamics and chemistry driven in part by significant alterations in the faunal community.